Investigation on the mechanical behavior of polyester-scrap tire composites. (30th November 2016) - Abu-Jdayil, Basim; Mourad, Abdel-Hamid I.; Hussain, Atif
Graphical abstract: Highlights: Development of scrap tires - based composites for thermal insulation. Two different rubber sizes and nine concentrations are considered. Investigation of the rubber-polyester composites mechanical stability. Rubber-polyester composites toughness reduces with rubber concentration. Good insulator mechanical integrity is achieved. Abstract: An investigation of the mechanical properties of unsaturated polyester composites containing rubber waste particles is presented. The main objective of this work was to formulate and develop polyester-rubber composite as an insulating material with acceptable mechanical performance. To determine the effect of the rubber particles ratio on the compressive and tensile strengths and moduli of a polyester composite 8 different concentrations (i.e., 5%, 10%, 15%, 20%, 25%, 30%, 35% and 40% by volume) were considered. The experimental results revealed that mixing rubber particles with the polyester matrix decreased both the compressive and tensile strengths and moduli of the composite. As the rubber content increases, and due to its low hydrophilicity towards polyester resin, the degree of crosslinking between the rubber particles and polyester is reduced causing a noticeable reduction in the composite strengths. On the other side for all investigated rubber contents, the larger the particle size of rubber, the lower the composites strength and modulus of elasticity. This is due to the difficulty of dispersion of the large particles into the matrix resulting non homogenous distribution of the particles and less interfacial contact with the matrix and in turn degradation in the mechanical behavior. However, smaller rubber particles have more specific surface area that could improve the interfacial contact with the polyester matrix. The SEM micrographs indicated that voids within the composite matrix increased with the content and size of rubber particles. Though adding rubber particles reduces the mechanical properties, the prepared composites demonstrate superior mechanical tensile strengths (22.8–1.25 MPa) and compressive strength (79.5–8.42 MPa) if compared with the currently used insulating materials and comparable to some construction materials like the stone masonry.